2012
DOI: 10.1073/pnas.1121203109
|View full text |Cite
|
Sign up to set email alerts
|

Modeling disease mutations by gene targeting in one-cell mouse embryos

Abstract: Gene targeting by zinc-finger nucleases in one-cell embryos provides an expedite mutagenesis approach in mice, rats, and rabbits. This technology has been recently used to create knockout and knockin mutants through the deletion or insertion of nucleotides. Here we apply zinc-finger nucleases in one-cell mouse embryos to generate disease-related mutants harboring single nucleotide or codon replacements. Using a gene-targeting vector or a synthetic oligodesoxynucleotide as template for homologous recombination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 37 publications
(64 reference statements)
3
48
0
Order By: Relevance
“…We observed TALEN-mediated induction of NHEJ in 25.4% of the offspring independent of targeting construct integration. These results are in line with efficiencies reported for zinc-finger nucleases in mice [25][26][27] and rats 28 , as well as for TALEN-injections in murine oocytes 6,12,13,29 . Newly established methodology using the CRISPR/Cas9 system to induce DNA double-strand breaks and facilitate homologous recombination 21,22 certainly raises high expectations that this system could also be used to mediate homologous recombination of larger donor plasmids directly in oocytes 22 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We observed TALEN-mediated induction of NHEJ in 25.4% of the offspring independent of targeting construct integration. These results are in line with efficiencies reported for zinc-finger nucleases in mice [25][26][27] and rats 28 , as well as for TALEN-injections in murine oocytes 6,12,13,29 . Newly established methodology using the CRISPR/Cas9 system to induce DNA double-strand breaks and facilitate homologous recombination 21,22 certainly raises high expectations that this system could also be used to mediate homologous recombination of larger donor plasmids directly in oocytes 22 .…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, the rate of correctly ARTICLE recombined clones was increased if both TALENs and the targeting construct were transfected together. From these observations we conclude that the construct integration rate in oocytes, and the resulting frequency of homologously mutated animals, although slightly lower than reported (for example, for the ROSA26 locus using zinc-finger nucleases), is still within an acceptable range given the size of the targeting construct [23][24][25][26] . We observed TALEN-mediated induction of NHEJ in 25.4% of the offspring independent of targeting construct integration.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, although introgression of the GDF8 821del11 allele with rAAV was efficient, viral methods are unlikely to be popular with consumers of animal protein. Recent studies have demonstrated that single-stranded oligonucleotides (oligos) 40-100 nt in length could serve as effective templates for HDR when stimulated by double-strand breaks (DSBs) in DNA (20,21,(29)(30)(31). Accordingly, we sought to determine whether this approach could stimulate HDR in primary fibroblasts from pigs and cattle, cellular substrates suitable for the creation of gene-edited animals by cloning.…”
Section: Significancementioning
confidence: 99%
“…These data suggest that Hoxb1 and Hoxa1 are more phenotypically divergent than previously reported and support that sub-and/or neofunctionalization has occurred in these paralogous genes leading to a divergence of gene function and incomplete redundancy. Furthermore, this study highlights the importance of obtaining fitness measures of mutants in ecologically relevant conditions to better understand gene function and evolution.KEYWORDS fitness assay; functional redundancy; Hoxa1; Hoxb1; intraspecific competition; subfunctionalization G ENE targeting techniques have led to the phenotypic characterization of thousands of genes across eukaryotes (for reviews see Thorneycroft et al 2001;Capecchi 2005;Collins et al 2007) and this characterization continues as this invaluable technology develops (e.g., Meyer et al 2012;Hsu et al 2014). However, an estimated 10-15% of mouse genes show minimal to no phenotypic consequences when disrupted (mouse appears normal), despite many having highly conserved sequences (Barbaric et al 2007).…”
mentioning
confidence: 99%
“…KEYWORDS fitness assay; functional redundancy; Hoxa1; Hoxb1; intraspecific competition; subfunctionalization G ENE targeting techniques have led to the phenotypic characterization of thousands of genes across eukaryotes (for reviews see Thorneycroft et al 2001;Capecchi 2005;Collins et al 2007) and this characterization continues as this invaluable technology develops (e.g., Meyer et al 2012;Hsu et al 2014). However, an estimated 10-15% of mouse genes show minimal to no phenotypic consequences when disrupted (mouse appears normal), despite many having highly conserved sequences (Barbaric et al 2007).…”
mentioning
confidence: 99%